Development of Multicultural-Based Quartet Card Learning Media for Civic Education Subject of Fourth-Grade Elementary School - Liry Amilleanda; Nina Nurhasanah; Evita Adnan (Universitas Pendidikan Indonesia Kampus Serang, 2022)
This research investigated the development of the multicultural-based Quartet Card learning media for Civic Education Lesson for fourth-grade Elementary Schools. Elementary school education level has an important role in shaping the young generation of Indonesia who has high knowledge and understanding of the cultural diversity of the Indonesian nation, this research aimed at producing learning media that can be an alternative solution to help elementary school students identify and implement values of multicultural values in Indonesian society diversity. This research and development adapted the ADDIE development model which consists of 5 stages: (1) Analysis (2) Design (3) Development (4) Implementation (5) Evaluation. To determine the validity of this learning media, an expert test was conducted by three experts, namely experts in media, experts in material, and linguists. Meanwhile, to find out the responses from students, two stages of testing were carried out, namely the one-to-one trial stage and the small group trial stage. The validation results of the multicultural-based Quartet Card learning media gained a score of 95.23% for the media, 90% for the material, and 97.91% for the language. The results of the students' test obtained a value of 93.33% for the one-to-one trial and obtained a value of 96.02% for the small group trial. Based on these results, the learning media that has been developed is suitable for use in the Civics learning process in fourth-grade Elementary School, so that it can have implications for helping students understand the material